CYTOTOXIC COMPOUND FROM ETHYL ACETATE FRACTION OF Brucea javanica (L.) Merr FRUIT AGAINST HeLa CELL LINE - Nurlina Nurlina; Ari Widiyantoro (Alchemy)
The pure compound relatively (85 mg) was isolated from 4.5 kg Brucea javanica (L.) Merr. fruits sample. It was obtained from ethyl acetate fraction as a red-brownish amorphous solid of melting point 202-206 oC. Phytochemical screening of isolate showed positive result of terpenoid group. Based on analysis by UV, IR,1H-NMR and 13C-NMR spectroscopy and by comparison with known related compounds, indicated that isolate is quassinoid compound named Picras 3- en- 21- oat acid, 15-(acetyloxy)-13,20- epoxy-3-(ß-D- glucopyranosyloxy)-11, 12- dihydroxy -2, 16- dioxo -, methyl ester. Cytotoxic test using MTT assay method showed that compound have IC50 9,7 µg/mL.